If it's not what You are looking for type in the equation solver your own equation and let us solve it.
g+19/6=7
We move all terms to the left:
g+19/6-(7)=0
determiningTheFunctionDomain g-7+19/6=0
We multiply all the terms by the denominator
g*6+19-7*6=0
We add all the numbers together, and all the variables
g*6-23=0
Wy multiply elements
6g-23=0
We move all terms containing g to the left, all other terms to the right
6g=23
g=23/6
g=3+5/6
| .1/1.5=2/x | | (x+3)/3=8 | | 27+54=c^2 | | -12=n26 | | −2+4(4a+2)=18+4(3a+2) | | 1.6z+10=0.7z+64 | | 18-6x=2x-6 | | 3(h−66)=84 | | a÷5+4=14a= | | 19=d3+ 15 | | 41+5x=61 | | 96=31+5z | | 12-5y=22 | | 10m-17=63m= | | 5(x+10)+4x=3x+2 | | w−55=33 | | 12n−8+3n=52 | | 4(5m−1)=84 | | 210/n=46/10 | | 3(x+6)=3x+15 | | 12=r+3 | | x+16=13x | | 4(5w−1)=84 | | m/3.2=8m= | | 0.6x-1.9=02x+0.5 | | 24x=2,040 | | 2x+105=105 | | 20+10x+10=15x+20-4x | | 3a=21+30 | | 7(1-8x)=5x+7 | | 24=–6a–6 | | (1,06)^x=3 |